The Model of Pedagogical Work Differentiation in the Framework of the Teacher Training Modernization - Belyaeva, Tatiana Konstantinovna; Belinova, Natalya Vladimirovna; Novik, Irina Rafailovna; Shabanova, Tatiana Leonidovna; Shlyakhov, Mikhail Yurievich (International Review of Management and Marketing, 2016)
The aim of the article is the presentation of the authors' approach to pedagogical work differentiation based on educational activities of teachers at school of the future. The results of starkly new teacher training system implementation in pedagogical higher schools as part of an innovative strategic project "The teacher of the future" are introduced. The content and technology of students' training in accordance with new teaching specialties are in the focus. The model of pedagogical work differentiation and the corresponding system of future teachers training provides a number of advantages and the solution of key problems in the school system in Russia. It allows to: 1) make the system of teacher education significantly more open due to closer cooperation with school through the educational process at all levels; 2) to increase the prestige of the teaching profession, to provide a more flexible and mobile training methods for it; 3) to create the conditions for career prospects within the teaching profession; 4) to carry out the practical orientation of the teacher training from the earliest training stages, to make this process a particular school oriented; 5) to provide training according to the new paradigm of working school teachers who are ready to change and improve the quality of their teaching. Key words: corrector, moderator, tutor, subject teacher, meta-competence. JEL Classifications: I200; I21; J24